A Parallel and Distributed Approach to the Analysis of Time Series on Remote Sensing Big Data - de Oliveira, Sávio S. T.; Pascoal, Luiz M. L.; Cardoso, Marcelo de C.; Bueno, Elivelton F.; Rodrigues, Vagner J. S.; Martins, Wellington S. (Journal of Information and Data Management, 2019)
The era of Remote Sensing Big Data has arrived. Indeed, massive amounts of remotely sensed data have been collected by different countries from a large number of Earth observation spaceborne and airborne sensors. They allow us to identify meaningful changes in the Earth’s surface that may affect whole ecological systems and be a threat to biodiversity. Crucial to that end is time series analysis of remote sensing images, for which the Time-Weighted Dynamic Time Warping (TWDTW) algorithm stands out as one of the most used approaches found in the literature so far. However, the computational complexity of the TWDTW algorithm makes it rather inefficient for Remote Sensing Big Data. Also, the huge volume of high spatial-temporal resolution remote sensing data cannot be handled by a single computing node. To overcome that drawback, this work proposes a parallel algorithm, named SP-TWDTW (Spatial Parallel TWDTW), that allows for the analysis of large scale time series using Manycore architectures (GPU). In order to process massive time series of remote sensing data in a cluster of computers, an approach for distributing the TWDTW processing is introduced in this paper.